Sekolah Sehat dan Nyaman: Edukasi Ergonomi dan Sanitasi Lingkungan bagi Siswa SMK Muhammadiyah 1 Pekanbaru - Yoana Agnesia; Lailatul Syifa Tanjung; Sumianto Sumianto (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2025)
Schools must provide a healthy, clean, and comfortable environment to support students' learning processes. However, vocational schools often face issues such as poor sitting posture, inadequate ventilation, and low sanitation standards. This Community Service Program aimed to educate students at SMK Muhammadiyah 1 Pekanbaru on the importance of ergonomics and environmental sanitation to help create a healthy and comfortable school environment. The program was implemented in four stages: (1) socialization and education on proper sitting posture, lighting, ventilation, toilet hygiene, and waste separation; (2) student training on how to conduct simple ergonomic and sanitation audits in classrooms; (3) direct observation and group discussions to develop improvement recommendations; and (4) creation and installation of educational posters in strategic school areas. The results showed a 34% increase in students’ knowledge based on pre-test and post-test assessments, along with increased student awareness and initiative in maintaining their learning environment. This program demonstrated that participatory education in ergonomics and environmental sanitation can significantly enhance student awareness and engagement in creating a healthy school setting. It is expected to be the foundation for fostering a sustainable culture of health and comfort within the school.